Are Lone Mothers Responsive to Policy Changes? The Effects of a Norwegian Workfare Reform on Earnings, Education, and Poverty - Chiara Pronzato; Magne Mogstad (Statistics Norway, Research Department, 2008)
The generous Nordic model of welfare is commonly viewed as an exceptional success both in terms of equality and economic growth. However, it has recently become evident that subgroups of the population with weak labour market attachment and high welfare dependency, such as lone mothers, were vastly overrepresented among the poor. This motivated a workfare reform of the Norwegian welfare system for lone mothers; activity requirements were introduced, time limits imposed, and benefit levels raised. To evaluate the welfare reform we introduce an estimator that, unlike the much used difference-in-difference approach, accounts for the fact that policy changes are typically phased in gradually rather than coming into full effect at once. We find that the workfare reform did not only increase earnings and education as well as lower welfare caseloads and by this route ease the financial burden of the government, but also reduced poverty.
Keywords: C23; I32; I38; J00; 330; Welfare reform; lone mothers; difference-in-difference; workfare; activity requirements; time limits; earnings; education; poverty